FDI Trend and Its Contribution Toward Labor Absorption in East Java - Nur, Citra Fatimah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This study aims to examine and analyze the effect of investment through number of FDI project and amount of FDI capital toward labor absorption and its trend and distribution at East Java Province in Indonesia. The study period was eighteen years from 2000 to 2017 by using secondary data of Principal License issued by Indonesia Investment Board in the form of combination between times series data and crosssectional data (5 cities/regencies in East Java) also known as panel data. Hypothesis testing in this study is conducted by using Panel Data Regression Model under Eviews 7. Test of 2 (two) hypothesis with level of significance Î± = 0.05 obtained the following results: First, amount of FDI capital has a positive but not significance effect on labor absorption. Second, number of FDI project has a positive and significance effect on labor absorption. The distribution of FDI in East Java still in disparity, only spread in some big cities/regencies (Surabaya, Sidoarjo, Gresik, Pasuruan and Mojokerto) with sector preference about secondary industry such as chemical industry, metal industry, food industry, other industry and trade and reparation.